Engineering Education in an Industrial Context - Hagenreiner, Thomas; Engelmann, Grazia; Köhler, Peter (International Journal of Advanced Corporate Learning (iJAC), 2015)
Learning is a lifelong process, which may not end at the transition from school to work. To exploit modern software systems used in design engineering, in order to increase efficiency and stay competitive, engineers have to keep on gaining knowledge during occupation. Anyhow, employees are usually not or only insufficiently trained, as no working time shall be lost. This paper demonstrates an opportunity to implement a learning-by-doing within the development process by the utilization of a Knowledge Based Engineering System (KBES). The user is supposed to be able to improve efficiency and quality in design engineering without the need of time-consuming trainings. Instead he/she is getting a short introduction (10 to 15 minutes), which can take place anytime during work. Therefore, product- and process-knowledge is saved within a knowledge-base and provided to the user in a way allowing him/her to use the system intuitively as he/she is guided through the process. As each step of the system may be reconstructed in the structure tree of the CA-system, the user understands the basic concepts in an implicit way. An experimental study is conducted to prove the effects of the KBES. The results clearly show that the efficiency and data-quality can be raised by the usage of such a system. Furthermore the study proves that there is a learning effect as the test persons could improve their results on a more complicated task after about four to six weeks past the introduction. The results may be explained with the Cognitive-Load-theory regarding the method of Worked-Out-Examples.